BUILDING STUDENT LEARNING READINESS AND ENGAGEMENT THROUGH A PRE-PRESENTATION FEEDBACK STRATEGY IN HIGHER EDUCATION - Raudiyah Rizki R (Yayasan Amanah Nur Aman, 2026)
Learning readiness and student engagement are fundamental factors influencing the quality of teaching and learning in higher education. Nevertheless, group presentations are often conducted with limited preparation, resulting in superficial discussions, insufficient conceptual understanding, and the potential for misconceptions during classroom learning. This study aimed to explore how the Pre-Presentation Feedback Strategy (SUPP) fosters students' learning readiness and engagement by providing academic feedback prior to classroom presentations. A descriptive qualitative approach was employed at the Faculty of Tarbiyah and Teacher Training, Universitas Islam Negeri Sumatera Utara, Indonesia. The strategy was implemented across several undergraduate courses for more than two semesters, involving over 200 third-semester and senior students. Data were collected through classroom observations, semi-structured interviews with student representatives from each class, document analysis, end-of-course evaluations, and the lecturer's reflective notes. The data were analyzed using the interactive model of Miles, Huberman, and Saldaña. The findings reveal that SUPP enhanced students' learning readiness by encouraging systematic preparation, revision based on academic feedback, and deeper conceptual understanding before presentations. Furthermore, the strategy promoted higher levels of student engagement, as reflected in improved presentation quality, more active classroom discussions, greater self-confidence, and stronger academic responsibility. Students also reported a shift in perception, from initially viewing the strategy as demanding to recognizing its contribution to improving their learning experience. These findings suggest that the Pre-Presentation Feedback Strategy has the potential to foster a more reflective, collaborative, and improvement-oriented learning culture in higher education